Programa pós-creche e atendimento público municipal: um olhar para as condições da oferta de educação para a primeira infância - Costa, Beatriz Aparecida da [UNESP] (2014)
It has been investigated on this thesis a partnership program between municipal authorities and the private profitable institutions of education which aim is to care for children between 0 and 3 years old not contemplated by the structure of the municipal network. This program has been implemented in the state of São Paulo, being entitled Program Pró-Creche. We aim more specifically, to investigate the conditions of service provided to students who attend the municipal network of early childhood education and private schools of education subsidized by the public authority. For this we use the qualitative approach and the methodology of Case Study, and as instruments of data collecting: interviews, observations, collecting of documents and municipal institutions, bibliographic research and response of “Indicators Quality in Early Childhood Education” from the schools surveyed. Our sample summed up to three institutions of early childhood education: a municipal one, a private one-which attends only students originated from the Program Pró-Creche, and a private one, which, in addition to students funded by public authorities, it also included students whose parents pay the tuition charged by the institution. It has been concluded that the Program Pró-Creche is added to privatization process in the area of education, which has been growing within the municipality studied, undermining the conditions of educational attendance of first childhood and dissolving rights historically conquered in favor of early childhood education